Faktor-Faktor yang Mempengaruhi Keberterimaan Penggunaan Uang Digital di Masyarakat Kota Yogyakarta Dengan Menggunakan Model TAM - Kurniawan, Taufan Adi; Endahjati, Supeni (Politeknik Caltex Riau, 2020)
Electronic money or e-money is not a new thing in the industrial world. Indonesia already has clear permit regulations for the use of digital funds in everyday transactions, only the last few years the general public has begun to slowly switch from physical money to electronic money, both for shopping, paying for accounts, using toll services and various other needs. But there are some people who are still reluctant to switch to electronic money and still using physical money. This study aims to analyze the factors that influence society in using electronic money in everyday transactions at Yogyakarta city using the technology acceptance model (TAM). Research is quantitative by using purposive sampling convenience.